Effect of dietary vitamin a supplementation on serum and liver retinol content, growth performance, carcass composition, and meat quality of lambs and cattle - Arnett, Aaron Matthew (Kansas State University, 2007)
Two experiments were conducted to evaluate the effects of dietary vitamin A on growth, carcass characteristics, and meat quality of ruminants. In Experiment 1, 40 crossbred wethers (BW = 28.7 kg) were assigned to 1 of 4 treatments: backgrounding (BG) and finishing (FN) with no vitamin A (LL); BG with no vitamin A, FN with high vitamin A (6,600 IU[dot in middle of line]kg [superscript-1] diet) (LH); BG with high vitamin A and FN with no vitamin A (HL); and BG and FN with high vitamin A (HH). During BG (d 1 to 56), intake was restricted to achieve 0.22 kg ADG. During FN (d 57 to 112), lambs consumed the same diet ad libitum. Lambs were humanely slaughtered after 112 d. There were no treatment differences (P > 0.05) in feed intake, ADG, or final BW. Carcasses from the HH group had higher (P < .05) marbling scores (514 vs. 459), and 25.8 % more extractable intramuscular lipid (IMF) than LL (3.88 vs. 3.08 % for HH and LL, respectively, P < .05); the LH and HL treatments were intermediate. The was a negative correlation (r = -0.38) between serum fatty acid content and %IMF. Experiment 1 data suggest that increased marbling may be achieved with high vitamin A for 112 d in lambs. In Experiment 2, Angus crossbred steers (n = 48), were either early-weaned (EW) at 137[plus or minus]26 d of age or weaned at a traditional age (TW) 199[plus or minus]26 d and allotted to either 42,180 IU vitamin A[dot in middle of line]hd[superscript-1][dot in middle of line]d[superscript-1] (HA) or no vitamin A (NA). Early- and TW steers consumed treatments for 235[plus or minus]17 and 175[plus or minus]18 d, respectively. Serum and liver retinol content diverged dramatically (both, P < 0.01) by the end of the experiment and TW steers tended (P > 0.10) to have higher ADG than EW steers (1.31[plus or minus]0.2 and 1.48[plus or minus]0.2 kg[dot in middle of line]hd[superscript-1][dot in middle of line]d[superscript-1], respectively). Steers were humanely slaughtered at 1.02 cm fat. Weights tended (P = 0.08) to be heavier and carcasses were fatter (P < 0.05) for HA than NA. Marbling score and % IMF were higher (P < 0.05) for EW-NA than other treatments. Percentage of USDA Choice and Prime carcasses doubled (P < 0.05) for NA than HA. Yield grades increased (P < 0.05) with EW-HA and were similar (P > 0.10) among other treatments. Feeding NA was effective for increasing marbling without increasing fat; EW enhanced these effects. Reasons for the contradictory results in these 2 experiments are unclear. Species differences in the ability to metabolize retinol are implicated.
Keywords: Cattle; Lamb; Vitamin A; Marbling; Early weaning; Meat quality; Agriculture, Animal Culture and Nutrition (0475)